2000
DOI: 10.1007/s100960000346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Evaluating a New Hub Device Designed to Prevent Catheter-Related Sepsis

Abstract: A new commercial hub device designed to minimise catheter-related infections was evaluated in a prospective, randomised trial in the intensive care and surgical units of the Hospital de Tortosa Verge de la Cinta in patients in whom the central venous catheters were expected to remain indwelling for at least 7 days. The assessments conducted at catheter withdrawal included cultures of the skin at the catheter site and cultures of the catheter tip and the catheter hubs; moreover, in cases of suspected catheter-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…A novel CVC hub developed by Segura et al [57] contains a connecting chamber filled with iodinated alcohol and was shown in a randomized clinical trial to be associated with greatly reduced rates of CVC-related BSI (4% vs 16%, P = < 0.01), although a subsequent trial failed to show benefit with the novel hub [58]. Although noncuffed CVCs were studied in these trials, the catheters remained in place for much longer than is usual in US ICUs, amplifying the importance of the intraluminal route of CVC-related BSI.…”
Section: Anti-infective Hubsmentioning
confidence: 98%
“…A novel CVC hub developed by Segura et al [57] contains a connecting chamber filled with iodinated alcohol and was shown in a randomized clinical trial to be associated with greatly reduced rates of CVC-related BSI (4% vs 16%, P = < 0.01), although a subsequent trial failed to show benefit with the novel hub [58]. Although noncuffed CVCs were studied in these trials, the catheters remained in place for much longer than is usual in US ICUs, amplifying the importance of the intraluminal route of CVC-related BSI.…”
Section: Anti-infective Hubsmentioning
confidence: 98%
“…A hub including an iodinealcohol reservoir was shown to reduce CR-BSI fourfold in one study, 31 but failed to show benefit in a more recent investigation. 32 In randomised controlled trials in adult patients, catheters externally impregnated with chlorhexidinesilver sulphadiazine have been shown to reduce the incidence. [33][34][35] Coating both the internal and external catheter surfaces with minocycline and rifampicin significantly reduces the risk of colonisation and CR-BSI, 36 although this protection is short lived as the antibiotics are washed off.…”
Section: Preventionmentioning
confidence: 99%
“…For the temporary catheters, the entry of the pathogen to the catheter can be through the exit site and the tunnel around the catheter (extraluminal hypothesis) [9][10][11]. Among the well-known preventive measures for CRB are the use of strict hygiene measures during placement and maintenance of the catheters, the application of preventive antimicrobial ointments/solutions at the exit site, the eradication of a Staphylococcus aureus nasal/skin carrier state, the cleansing of catheter hubs with antimicrobial solutions, the use of antimicrobial-coated catheters, and the intraluminal application of antibiotic lock solutions (ABLs) [5,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%